2007
DOI: 10.1182/blood-2006-11-057521
|View full text |Cite
|
Sign up to set email alerts
|

Nilotinib exerts equipotent antiproliferative effects to imatinib and does not induce apoptosis in CD34+ CML cells

Abstract: Chronic myeloid leukemia (CML) stem and progenitor cells overexpress BcrAbl and are insensitive to imatinib mesylate (IM). We therefore investigated whether these cells were efficiently targeted by nilotinib. In K562, the inhibitory concentration (IC50) of nilotinib was 30 nM versus 600 nM for IM, consistent with its reported 20-fold-higher potency. However, in primary CD34(+) CML cells, nilotinib and IM were equipotent for inhibition of BcrAbl activity, producing equivalent but incomplete reduction in CrkL ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
214
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(229 citation statements)
references
References 20 publications
14
214
1
Order By: Relevance
“…18 In addition, incomplete inhibition of BCR-ABL kinase activity in CML CD34 þ cells after imatinib treatment has previously been demonstrated. 11,31 Hence, we speculate that reduced intracellular accumulation of imatinib in primitive CML CD34 þ and CD34 þ 38À cells, mediated through a reduced OCT-1 Activity, may contribute to incomplete imatinib-induced BCR-ABL kinase inhibition, and thus increased survival of these cells, 32 Low OCT-1 Activity in CML CD34 þ cells JR Engler et al compared with more mature counterparts. Notably, a number of studies have shown that primitive CD34 þ 38À and CD34 þ 38 þ cells express increased BCR-ABL transcripts compared to their more mature counterparts.…”
Section: Iur Of Imatinib and Oct-1 Activity In CML Cellsmentioning
confidence: 99%
“…18 In addition, incomplete inhibition of BCR-ABL kinase activity in CML CD34 þ cells after imatinib treatment has previously been demonstrated. 11,31 Hence, we speculate that reduced intracellular accumulation of imatinib in primitive CML CD34 þ and CD34 þ 38À cells, mediated through a reduced OCT-1 Activity, may contribute to incomplete imatinib-induced BCR-ABL kinase inhibition, and thus increased survival of these cells, 32 Low OCT-1 Activity in CML CD34 þ cells JR Engler et al compared with more mature counterparts. Notably, a number of studies have shown that primitive CD34 þ 38À and CD34 þ 38 þ cells express increased BCR-ABL transcripts compared to their more mature counterparts.…”
Section: Iur Of Imatinib and Oct-1 Activity In CML Cellsmentioning
confidence: 99%
“…Accumulating evidence has now shown that very primitive CML cells in the chronic phase are relatively unresponsive to IM and, in fact, to many tyrosine kinase inhibitors both in vitro and in vivo. 17,18,95 These rare leukemic cells also share in their possession of multiple unique features that would be expected to promote both common and acquired mechanisms of resistance to BCR-ABL-targeted therapeutics. 19,20,22,[96][97][98][99][100] The latter include the greatly increased expression of BCR-ABL in primitive (CD34 þ CD38 À ) CML cells (a 4100-fold increase in transcripts and a 3-10-fold increase in protein and kinase activity) that appears to be independent of the cycling status of the cells.…”
Section: Properties That Affect Responses To Bcr-abl-targeted Therapementioning
confidence: 99%
“…In primary CML CD34+ cells, Imatinib-induced apoptosis is preceded by Bim accumulation; this effect was decreased when cells were cultured in a cytokine-containing medium [78]. In contrast to Imatinib, whose main effect on CML cells seems to be induction of apoptosis, the predominant effect of nilotinib seems to be antiproliferative -rather than apoptotic [17]. Indeed, it has been suggested that Nilotinib can induce a G 0 /G 1 cell cycle blockade in cells expressing wild type Bcr-Abl, which could result in disease persistence [79].…”
Section: Nilotinibmentioning
confidence: 99%
“…In this regard, several studies have shown that TKIs, like Imatinib, Nilotinib, Dasatinib, Bosutinib, and Lonafarnib, have antiproliferative or apoptotic effects in almost all dividing CML cells; however, the population of stem cells remains viable in a quiescent state [16][17][18][19][20][21].…”
Section: Leukemic Stem Cells In Chronic Myeloid Leukemiamentioning
confidence: 99%